2007
DOI: 10.3844/jcssp.2007.119.121
|View full text |Cite
|
Sign up to set email alerts
|

SMS for Question-Answering in the m-Learning Scenario

Abstract: Emerging technologies are leading to the development of several new opportunities to guide and enhance learning that were unimaginable a few years ago. The move towards adopting mobile learning technologies is fast growing in both academic and industrial sectors. Mobile learning uses portable devices linked to a commercial public network, including different types of mobile phones and handheld computers. For mobile users, as well in all mobile applications, SMS messaging is found to be the most useful and conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…8 The literature shows recent efforts in other social service fields, notably public health, to exploit SMS for the delivery of helpful information at point of need: to bulimic undereaters 9 and to overeaters, 10 to people quitting smoking 11 or undergoing other forms of behavior modification, 12 in epidemiological data collection, 13 and in helping people avoid sexually transmitted diseases. 14 SMS is also finding a place in the mobile learning arena 15 and for helping students orient to and get useful information about their university. 16 The Nielsen survey found American's text message traffic increased by 350% in a single year.…”
Section: The Evolving Communications Ecosystemmentioning
confidence: 99%
“…8 The literature shows recent efforts in other social service fields, notably public health, to exploit SMS for the delivery of helpful information at point of need: to bulimic undereaters 9 and to overeaters, 10 to people quitting smoking 11 or undergoing other forms of behavior modification, 12 in epidemiological data collection, 13 and in helping people avoid sexually transmitted diseases. 14 SMS is also finding a place in the mobile learning arena 15 and for helping students orient to and get useful information about their university. 16 The Nielsen survey found American's text message traffic increased by 350% in a single year.…”
Section: The Evolving Communications Ecosystemmentioning
confidence: 99%
“…The finding of this research showed that, each of the six factors had significant effect on learner's satisfaction. Many authors discussed evaluation of e-learning system from pedagogical prospective in (Balasundaram and Ramadoss, 2007;Pruengkarn and Srivihok, 2005;Yunus and Salim, 2008;Britain, 1999;Wang and Wang, 2009). Authors in (Ardito et al, 2006) proposed a good methodology, called eLSE (e-learning Systematic Evaluation) based on inspection technique.…”
Section: Types Of E-learningmentioning
confidence: 99%
“…Although, most QA systems are based on Web environments, SMS has also been used as an environment in contexts such as in learning [8] and agriculture [9].…”
Section: Introductionmentioning
confidence: 99%